Genomic Analysis Suggests KITLG is Responsible for a Roan Pattern in two Pakistani Goat Breeds. (28th October 2017) - Talenti, Andrea; Bertolini, Francesca; Williams, Jamie; Moaeen-ud-Din, Muhammad; Frattini, Stefano; Coizet, Beatrice; Pagnacco, Giulio; Reecy, James; Rothschild, Max F; Crepaldi, Paola; ,
Abstract: The roan coat color pattern is described as the presence of white hairs intermixed with pigmented hairs. This kind of pigmentation pattern has been observed in many domestic species, including the goat. The molecular mechanisms and inheritance that underlie this pattern are known for some species and the KITLG gene has been shown associated with this phenotype. To date, no research effort has been carried out to find the gene(s) that control(s) roan coat color pattern in goats. In the present study, after genotyping with the GoatSNP50 BeadChip, 35 goats that showed a roan pattern and that belonged to two Pakistan breeds (Group A) were analyzed and then compared to 740 goats of 39 Italian and Pakistan goat breeds that did not have the same coat color pattern (Group B). Runs of homozygosity-based and XP-EHH analyses were used to identify unique genomic regions potentially associated with the roan pattern. A total of 3 regions on chromosomes 5, 6, and 12 were considered unique among the group A versus group B comparisons. The A region > 1.7 Mb on chromosome 5 was the most divergent between the two groups. This region contains six genes, including the KITLG gene. Our findings support the hypothesis that the KITLG gene may be associated with the roan phenotype in goats.